Influence of stretching exercises, warm-up, or cool-down on the physical performance of Mangalarga Marchador horses - Farinelli, F.; Carneiro de Rezende, A. S.; Gonçalves Fonseca, M.; Quintao Lana, A. M.; de Oliveira Paes Leme, F.; de Oliveira Nacif Klein, B.; Silva, R. H. P.; Pereira de Abreu, A.; de Jesus Damazio, M.; Martins Melo, M. (Journal of Equine Veterinary Science, 2021)
The Horse Agribusiness Complex is an important activity in the Brazilian agricultural sector. Mangalarga Marchador (MM) is the most numerous breed of horses in Brazil and its temperament and gait characteristics (4-beat stepping gait) allow for the constant growth of the breed and the performance of vs. equestrian activities. The training management currently adopted with MM horses is based on empiricism, and scientific support is necessary to improve the well-being of horses in competitions and maintain the physical integrity of these athletes. Therefore, this study aimed to verify the effects of stretching, warming up, and/or cooling down on their performance in marcha tests. 6 MM geldings (aged between 3 and 7 years and average weight of 400 kg) were used. The pre-experimental stage for the physical conditioning of the horses lasted 46 days. The experimental phase lasted 42 days and consisted of 6 marcha tests performed every 7 days. The experimental design was in a Latin square (6 × 6), in which each horse was submitted to the following exercise protocols: A) 50-min marcha test following the official regulations of the Brazilian Association of Horse Breeders Mangalarga Marchador (ABCCMM); B) 10 min of warm-up before marcha test; C) 10 min of cooling after marcha test; D) 10 min of warm-up before marcha and 10 min of cool-down after marcha test; E) 10 min of stretching before the marcha test; F) 10 min of stretching, 10 min of warm-up before and 10 min of cool-down after the test. Horses were evaluated before and after marcha tests for heart rate (HR), respiratory rate, rectal temperature, glucose, lactate, creatine kinase, aspartate aminotransferase and cortisol. Data were submitted to 2-way analysis of variance (exercise protocols and evaluation moments) and means were compared by Tukey's test (P=0.05). The HR and blood lactate results indicated a beneficial effect of warm-up or stretching practices on the performance of Mangalarga Marchador horses submitted to simulated marcha tests in accordance with the official ABCCMM regulation and lasting 50 minutes.